Elevated cardiac troponin predicts 11-year mortality in COPD - Nilsson, Ulf; Mills, Nicholas; Backman, Helena; Stridsman, Caroline; Hedman, Linnea; Rönmark, Eva; Blomberg, Anders; Lindberg, Anne (The European respiratory journal, 2020)
Background: Ischemic heart disease (IHD) is a common multimorbidity in individuals with COPD. High sensitive cardiac troponin I (hs-cTnI) has been shown to predict short-term mortality, but longer follow-ups has rarely been performed in population-cohorts. Aim: To evaluate the predictive value of elevated hs-cTnI on mortality among individuals with COPD compared with normal lung function (NLF). Methods: In 2002-04, subjects with FEV1/VC <0.70 (COPD, n=993) and age and sex-matched referents withoutCOPD were identified from OLIN’s population-based cohorts. In 2005, structured interviews, post-bronchodilator spirometry, blood sampling and ECG were performed in individuals with COPD (n=599) and NLF (n=756). Hs-cTnI was analysed in serum and concentrations ≥5 ng/L were defined as elevated. Mortality data were collected until 2016. Results: In 2005, the prevalence of reported IHD and elevated hs-cTnI was higher in COPD than NLF (16.2% vs 11.9% p=.02 and 31.1% vs 25.0% p=.01). The cumulative mortality was higher in COPD than NLF, both overall (36.5% vs 19.2% p<.001), and when restricting comparison to individuals with hs-cTnI≥5 (59.1% vs 34.9% p<.001). In a Cox-regression model adjusting for common confounders including reported IHD and ischemic ECG changes, hs-cTnI≥5 was associated with an increased risk for death in COPD (HR 1.41, 95%CI 1.03-1.93), but not in NLF (HR 0.84 95%CI 0.58-1.22). The increased risk remained after adjusting for FEV1% predicted. Conclusion: Elevated hs-cTnI was associated with increased mortality over a 11 -year follow-up among individuals with COPD, but not among those with NLF in this population-based study. The use of troponin could identify individuals with stable COPD at the highest risk of death.